Microstructure and mechanical properties of cold drawn AISI 1016 steel processed by ECAP - Marulanda, D. M.; Grupo de investigación REM-Research in Energy and Materials, Universidad Antonio Nariño, Bogotá, Colombia. (2014)
Low carbon cold drawn steel was deformed using equal channel angular pressing to evaluate its mechanical properties and microstructure, while assessing the possibility of improving properties beyond the cold drawn process. We used low carbon cold drawn steel with a composition of 0.16% C, 0.8% Mn, 0.2% Si, 0.02% P, 0.012% S and Fe balance. The process was carried out at room temperature and four passes at route Bc with a deformation of ~0.6 in each pass. Using scanning electron microscopy and x-ray diffraction, we evaluated the evolution of the structure before and after deformation as well as the mechanical properties of microhardness and tensile strength. A slight increase in the mechanical properties occurred when the number of passes was increased. There were changes in the original ferritic-pearlitic structure with the refinement of ferrite grains and pearlite deformation.